2016
DOI: 10.1098/rspa.2015.0689
|View full text |Cite
|
Sign up to set email alerts
|

A time-domain Kirchhoff formula for the convective acoustic wave equation

Abstract: Kirchhoff's integral method allows propagated sound to be predicted, based on the pressure and its derivatives in time and space obtained on a data surface located in the linear flow region. Kirchhoff's formula for noise prediction from high-speed rotors and propellers suffers from the limitation of the observer located in uniform flow, thus requiring an extension to arbitrarily moving media. This paper presents a Kirchhoff formulation for moving surfaces in a uniform moving medium of arbitrary configuration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Equation (2.12) is the integral solution to the acoustic analogy that considers the convection effect of oncoming flows. Similar processes in deriving the solution were also employed in several previous aeroacoustic studies (Najafi-Yazdi et al 2011;Ghorbaniasl, Siozos-Rousoulis & Lacor 2016;Zhong & Zhang 2017). For rotor noise, a remaining difficulty is considering the influences of unsteady motions in estimating the retarded time and |∂g/∂τ |.…”
Section: Formulations For Rotor Noise Computationmentioning
confidence: 99%
“…Equation (2.12) is the integral solution to the acoustic analogy that considers the convection effect of oncoming flows. Similar processes in deriving the solution were also employed in several previous aeroacoustic studies (Najafi-Yazdi et al 2011;Ghorbaniasl, Siozos-Rousoulis & Lacor 2016;Zhong & Zhang 2017). For rotor noise, a remaining difficulty is considering the influences of unsteady motions in estimating the retarded time and |∂g/∂τ |.…”
Section: Formulations For Rotor Noise Computationmentioning
confidence: 99%
“…It is known that the effects of mean flow incidence on a rotating source is equivalent to an unsteady acoustic source. 42 Also, from the linear acoustic theories, by converting the convective wave equation to a simple wave equation, it has been shown that there is some influence of uniform flow on overall noise levels. 42,43 From Figure 35, we can identify and confirm that some broadband contributions arise from the wake effects in the lower frequencies, but we cannot explicitly quantify this source.…”
Section: Near-field Acousticsmentioning
confidence: 99%
“…The fluid momentum equation (33) is converted to the Maxwell's equations by defining the 'fluid electric field', E ! , and the 'fluid magnetic field', B !…”
Section: The Electromagnetic Analogymentioning
confidence: 99%
“…A comprehensive treatment of the subject can be found in literature. [32][33][34] Of particular interest to this paper are the Kirchhoff acoustic velocity formulations, KV1 and KV1A, presented in literature. 34 The derivation of these results is based on Farassat's formulation 1 and 1 A solutions of equation 158for acoustic pressure.…”
Section: Dunnmentioning
confidence: 99%